Performance of a Recirculating Aquaculture System Utilizing an Algal Turf Scrubber for Scaled‐Up Captive Rearing of Freshwater Mussels (Bivalvia: Unionidae). (2nd October 2013) - Huang, Zhitao; Jones, Jess; Gu, Junye; Hallerman, Eric; Lane, Timothy; Song, Xiefa; Wan, Rong
Abstract: To develop a system supporting rapid growth of juvenile freshwater mussels, a recirculating aquaculture system was designed and built at the Laboratory for Conservation Aquaculture and Aquatic Ecology, Virginia Polytechnic Institute and State University. The system included a rectangular trough tank, a sump (biofilter), a pump, a microalgae drip feeder, and an air delivery system. An algal turf scrubber (ATS) was evaluated for its potential to maintain and improve water quality within the system. Growth and survival rates of juvenile rainbow mussels Villosa iris after 90 d were compared between system units with and without ATSs. Flow rate through the culture units was approximately 23.3 L/min. Results showed no statistically significant differences between the growth and survival rates of juvenile mussels reared in systems with ATSs and those reared in systems without ATSs. Ammonia and nitrite levels were low and did not differ among treatments. However, systems with ATSs exhibited significantly lower levels of nitrate and phosphate than systems without ATSs. Our results show that freshwater mussel culture systems can be scaled up to increase production and that the use of ATSs may help to maintain water quality in recirculating aquaculture systems during long‐term culture of freshwater mussels.